2012
DOI: 10.1016/s1995-7645(12)60092-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective effect of Acacia nilotica young seedless pod extract: Role of polyphenolic constituents

Abstract: The results of present study concluded that the hydroethanolic extract of young seedless pods of Acacia nilotica has antiulcer activity in pylorus ligation, swimming stress and NSAID induced rat ulcer models. The extract containing more amount of phenolic components show high antiulcer activity, indicating the phenolic component of the extract to be responsible for the activity of the extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 12 publications
1
28
0
1
Order By: Relevance
“…According to the results of a recent study, hydroethanol extract of young seedless pods of A. nilotica has antiulcer activity in pylorus ligation, swimming stress, and non-steroidal anti-inflammatory drugs induced rat ulcer models (Bansal & Goel, 2012). The results of a study clearly revealed that methanol and acetone extracts of A. nilotica (flowers) showed stronger anti-H. pylori activity than metronidazole, and almost the same activity as tetracycline.…”
Section: Acacia Niloticamentioning
confidence: 99%
“…According to the results of a recent study, hydroethanol extract of young seedless pods of A. nilotica has antiulcer activity in pylorus ligation, swimming stress, and non-steroidal anti-inflammatory drugs induced rat ulcer models (Bansal & Goel, 2012). The results of a study clearly revealed that methanol and acetone extracts of A. nilotica (flowers) showed stronger anti-H. pylori activity than metronidazole, and almost the same activity as tetracycline.…”
Section: Acacia Niloticamentioning
confidence: 99%
“…The results reflect the potential of fodder plants used by the indigenous people of Purulia district in animal husbandry. Earlier ethnobotanical excursions were carried out in the area and plants were reported as active against gastrointestinal problems, snake venom and as potential Chaudhary and Sotohy et al (1997) Gastroprotective (Bansal and Goel, 2012), Taparia (1990) antioxidant (Maldini et al, 2011) Ailanthus excelsa Roxb. Kumar (1999) Lavhale and Mishra Gastroprotective (Melanchauski et al, (2007) 2010), antihistaminic (Kumar et al, 2011) Anogeissus latifolia Kumar and Bhatt (2006) NCF Hepatoprotective (Pradeep et al, 2009), (Roxb.…”
Section: Resultsmentioning
confidence: 99%
“…[25] The antioxidant activity of the polyphenolic components were attributed mainly to their redox properties, which allow them to act as reducing agents, hydrogen donators, singlet oxygen quenchers and also have metal chelating properties. [26] However, in addition to their antioxidative property, polyphenolics also have other specific biological activities which are proven to be effective in the treatment of gastric ulcers, [27] cancer and cardiovascular disease. [28] Most of the Potentilla species such as P. fulgens, P. alba, P. fruticosa, P. freyniana, P. chinensis, P. fragarioides, P. viscose, P. erecta, P. anserina, P. argentea, P. aurea, P. palustris, P. reptans and P. tabernaemontani has been well proven scientifically to have antioxidant property in various in vitro and in vivo models.…”
Section: Phytoconstituentsmentioning
confidence: 99%